PENGARUH PELAKSANAAN REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PT. GREEN PLANET INDONESIA CABANG PEKANBARU - Ivan Fahrur; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the implementation of recruitment and job placement on employee performance partially and simultaneously. This study used a questionnaire as a data collection tool which was distributed to 95 respondents to employees of PT. Green Planet Indonesia Pekanbaru by conducting validity tests, reliability tests, simple linear regression analysis, multiple linear regression analysis, analysis of determination (R2) and hypothesis testing with t-test (partial) and F-test (simultaneous). ). The results showed that the first hypothesis testing is the implementation of recruitment on performance, namely t count (9.029) > t table (1.985), meaning that the implementation of recruitment has a significant effect on employee performance. Second, work placement is t count (12,147) > t table (1,985), meaning that work placement has a significant effect on employee performance. The results of the calculated F test (147.554) > F table (3.10) means that the implementation of recruitment and job placement simultaneously has a significant effect on employee performancebranch. The data was then processed using descriptive analysis and statistical analysis using SPSS 25 Keywords: Implementation of Recruitment, Work Placement, Employee Performance